Fracture: The Cross as Irreconcilable in the Language and Thought of the Biblical Writers. By Roy A. Harrisville - Howard Marshall, I. (The journal of theological studies, 2007)
Irreconcilable with what? The argument of this gripping book is that ‘with whatever “paradigm,” whatever theory, value or technique, with whatever language, conceptuality, way of viewing reality, or looking at the world the New Testament writers came to their encounter with the gospel of Jesus Christ, the death of Jesus forced them to a drastic revision. The “fracture” of language and conceptuality, the “depotentiation” in Paul, in the Gospel writers, in Hebrews, and in I Peter, attests to the discontinuity between the deed of the cross and the old constellations of theory and practice—all of it a reflex of the divine initiative in sending Jesus to his cross’ (p. 275). The author, who taught at Luther Seminary in St.